On the decentralized provision of public goods with spillovers in the presence of household mobility - Dietmar Wellisch (Eberhard Karls Universität Tübingen, Wirtschaftswissenschaftliche Fakultät, 1992)
When households are immobile among regions, the decentralized provision of public goods that generate interregional benefit spillovers is inefficiently low. A model of interregionial migration is used to study the provision of such services in the presence of free mobility of households. Within this model we find a surprising result: the Nash-equilibrium of competing regional governments is socially efficient. Though only maximizing the utility of their own residents, regional governments perfectly internalize the externalities associated with their provision of public goods. There is no role for a higher-level government to encourage the supply of public goods by a Pigovian subsidy.
Keywords: 330